2014
DOI: 10.1111/jvim.12269
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam Rectal Administration in Healthy Dogs

Abstract: BackgroundLevetiracetam is used to manage status epilepticus (SE) and cluster seizures (CS) in humans. The drug might be absorbed after rectal administration and could offer a practical adjunct to rectal administration of diazepam in managing SE and CS.HypothesisLevetiracetam is rapidly absorbed after rectal administration in dogs and maintains target serum concentrations for at least 9 hours.AnimalsSix healthy privately owned dogs between 2 and 6 years of age and weighing 10–20 kg.MethodsLevetiracetam (40 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…We performed rectal administration of sildenafil ODF formulation, which is rapidly absorbed in the mucous membranes [ 12 ]. Some studies have reported rectal administration of medication as an alternative route for dogs that are not able to receive medication orally because of seizure [ 13 , 14 ]. However, previous studies demonstrated that the dosage for rectal administration should be adjusted because C max and AUC last (an indicator of bioavailability) after rectal dosing is relatively lower than that after oral administration.…”
Section: Discussionmentioning
confidence: 99%
“…We performed rectal administration of sildenafil ODF formulation, which is rapidly absorbed in the mucous membranes [ 12 ]. Some studies have reported rectal administration of medication as an alternative route for dogs that are not able to receive medication orally because of seizure [ 13 , 14 ]. However, previous studies demonstrated that the dosage for rectal administration should be adjusted because C max and AUC last (an indicator of bioavailability) after rectal dosing is relatively lower than that after oral administration.…”
Section: Discussionmentioning
confidence: 99%
“…In a small study of elderly people with nonconvulsive and convulsive SE, levetiracetam effectively terminated seizure activity when used as a first‐line treatment . Recently, target serum concentrations of levetiracetam were achieved after rectal administration in 6 healthy dogs, with the only adverse effect being mild and transient sedation …”
Section: Anticonvulsant Therapymentioning
confidence: 99%
“…The C max was 36.0 ± 10.7 μg/mL and the T max 103 ± 31 min. Mild sedation was observed between 60 and 90 min, without other adverse effects noted [69].…”
Section: Hydantoins: Phenytoin and Fosphenytoinmentioning
confidence: 98%